Pengaruh Kepemimpinan Camat Terhadap Efektivitas Kerja Pegawai (Studi Pada Kantor Camat Bubon Kabupaten Aceh Barat) - Anisa Mahira; Zuhrizal Fadhly (Journal of Social and Policy Issues, 2021)
A leader must be a good example and role model for his subordinates in completing his work, because all actions, behavior, and policies of a leader greatly affect the performance of his subordinates. The aim of this article is to examine the influence of a sub-district head on the work efficiency of his subordinates at the Bubon Regional Office, West Aceh. The research used quantitative research techniques with correlational calculations which emphasizes the analysis of statisticsdata. The results showed that the correlation between the influence of a sub-district head and the work effectiveness of the Bubon sub-district office employees was 0.826 (R) which means that the correlation between the sub-district leadership style and the employee work effectiveness at the Bubon sub-district office has a very close relationship. In this study, every change in the influence variable of a sub-district head by 1 point will affect the change in the work effectiveness of the Bubon sub-district office employee by 8.261 points. It showed that a sub-district head does have an influence on increasing the effectiveness of employees' work at the bubon sub-district office.